.NET Web Services Solutions. - Jamsa, Kris (John Wiley & Sons, 2006)
.NET Web Services Solutions offers just what its title states: practical solutions to the real challenges you face as you use .NET to create applications that communicate with web services and--more to the point--to build and deploy web services of your own.